Is the six-minute walk test still reliable compared to cardiopulmonary exercise test for exercise capacity in children with congenital heart disease? - Jiangbo Qu; Hui Shi; Yugong Guo; Xinxin Chen; Xuwen Xiao; Xiaojuan Zheng; Yanqin Cui (Frontiers Media S.A., 2022)
ObjectivesWe aimed to assess the validity of the six-minute walk test (6MWT) to reflect the functional capacity of children with congenital heart disease (CHD), evaluate a possible correlation between the 6MWT distance with cardiopulmonary exercise test (CPET) variables, as well as to find a cutoff value to stratification the physical fitness in this population.MethodsWe enrolled 459 children with CHD, 6-18 years old, who performed a complete CPET and 6MWT on the same day in a cross-sectional observational study. Correlations between variables of CPET and six-minute walking distance (6MWD) were analyzed and cutoff values of 6MWD were identified for the classification of the physical fitness in the population.ResultsThe mean distance ambulated during the 6MWT was 578 ± 65 m, 590 ± 65 m for boys, and 562 ± 62 m for girls (p < 0.001). Both VO2max and %predicted VO2max showed a correlation with the 6MWT distance (r = 0.35, p < 0.001 and r = 0.51, p < 0.001, respectively), and an inverse correlation was found between VE/VCO2 slope and the 6MWT distance (r = −0.31; p < 0.001). There appeared to be a linear association between 6MWD and VO2max up to a 6MWD of approximately 600 m. We divided the population into 4 subgroups (boys <130 cm; boys ≥130 cm; girls <130 cm; girls ≥130 cm), and get the cutoff values (554 m, 617 m, 549 m, 587 m) respectively equivalent to 80% of predicted VO2max. The 6MWT distances of another 102 patients were applied for external verification of the cutoff values.ConclusionsOur study provided evidence on when a 6MWT should be considered as a convincing complementary test in the pediatric population with CHD and explored the classification of exercise tolerance using a 6MWD value. The cut-off values for 6MWD may be qualified as an intervention target for exercise rehabilitation.